2016
DOI: 10.1111/cdoe.12248
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric assessment of the short‐form Child Perceptions Questionnaire: an international collaborative study

Abstract: Objective To examine the factor structure and other psychometric characteristics of the most commonly used child oral‐health‐related quality‐of‐life (OHRQoL) measure (the 16‐item short‐form CPQ11‐14) in a large number of children (N = 5804) from different settings and who had a range of caries experience and associated impacts. Methods Secondary data analyses used subnational epidemiological samples of 11‐ to 14‐year‐olds in Australia (N = 372), New Zealand (three samples: 352, 202, 429), Brunei (423), Cambodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
(85 reference statements)
2
26
0
Order By: Relevance
“…The new split into 2 subscales, as we propose in this article, would produce 2 scores instead of 1 overall score and may reflect more accurately the properties of the instrument. This approach is consistent with the study done by Thomson and colleagues, 30 who suggested the same split of items to achieve psychometric accuracy. According to item response theory, 2 or 3 parameter models can take more parameters into account, such as guessing or the fact that items can vary in terms of location and discrimination.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The new split into 2 subscales, as we propose in this article, would produce 2 scores instead of 1 overall score and may reflect more accurately the properties of the instrument. This approach is consistent with the study done by Thomson and colleagues, 30 who suggested the same split of items to achieve psychometric accuracy. According to item response theory, 2 or 3 parameter models can take more parameters into account, such as guessing or the fact that items can vary in terms of location and discrimination.…”
Section: Discussionsupporting
confidence: 89%
“…As we could not fit the Rasch model because of strong indication of multidimensionality, which we describe in the Results section, we decided to split the instrument into 2 subscales according to the item development process published in literature: the results of a large international study (N ¼ 5,804) by Thomson and colleagues 30 in which the authors proposed 2 subscales instead of the originally hypothesized 4-factor structure, with social items and emotional items representing subscale 1, and functioning items and oral symptoms representing subscale 2. After rescoring 1 item, we reexamined the overall model fit, individual item functioning, and unidimensionality.…”
Section: Examination Of Individual Functioning Of Itemsmentioning
confidence: 99%
“…This is important for longitudinal studies and clinical trials, where responsiveness and reproducibility are key attributes, as it cannot be assumed that a measure shown to be reliable and valid in cross-sectional studies will necessarily be sensitive to changes over time in a clinical intervention. Therefore, if responsiveness is not demonstrated prior to its application, it is not sure whether this change is real or generated by measurement error [43,44]. On the other hand, developing strategies to facilitate the interpretation of scores (such as estimating the minimal important difference by using anchor-based or distributionbased strategies) may help to extend the use of these instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently investigated confounding factors were socio-demographic factors such as gender, household income and parents’ education. Because socio-demographic factors may influence OHRQoL, the nature and magnitude of impacts may in fact vary between populations of different cultural backgrounds [ 20 , 21 ]. Therefore, similar studies conducted in varying countries, including Lithuania, have their own inherent value and may be of interest.…”
Section: Introductionmentioning
confidence: 99%